Tricuspid endocarditis secondary to infection associated with a central venous catheter. Report of two cases - Salamanca, Max A. (2020)
Two patients with intravascular catheters who developed a serious complication such as infective endocarditis secondary to catheter-associated infection are described. These patients had a good resolution through antibiotic therapy and removal of the infected catheter without the need for cardiac surgery. Infections associated with the vascular catheter are frequent complications in carriers of vascular catheters that lead to possible serious consequences such as bacteremia or fungemia since they function as an entry point for germs that can infect a predisposed noble organ. Therefore, the present case report highlights the importance of considering endocarditis as a latent complication in patients with infectious risk associated with intravascular catheters and how to avoid the unnecessary use of a central venous catheter.